How Do Alliance Portfolio Factors Affect a Precision Medicine Firm’s Innovation Performance? - Yucheong Chon; Kwangsoo Shin (Journal of Open Innovation: Technology, Market and Complexity, 2021)
Precision medicine is an approach to disease treatment and prevention that seeks to maximize effectiveness by taking into account individual variability in genes, environment, and lifestyle. The medical paradigm has been changed with the emergence of precision medicine and many companies with business related to precision medicine should cooperate with other companies. The purpose of this study is to analyze the alliance portfolio factors that affect firms’ innovation performance. This study examined whether the diversity factors of the alliance portfolio and alliance management capability influenced its innovation performance. Additionally, we investigated the moderate effects of participation of research organizations in the alliance portfolio. As a result, there was an inverted U-shaped relationship between the industry diversity of the portfolio and innovation performance; therefore, the participation of research organizations in the alliance portfolio showed a positive effect. Additionally, the value governance diversity changed to have a positive effect by interacting with research organizations. This study provides information on the alliance portfolio factors that affect the innovation performance of precision medicine companies.